2019
DOI: 10.1080/20008198.2019.1679964
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance at pre-deployment is a significant predictor of post-deployment re-experiencing symptoms

Abstract: Background: Insomnia is common in service members and associated with many mental and physical health problems. Recently, longitudinal data have been used to assess the impact of disturbed sleep on mental health outcomes. These studies have consistently shown relationships between sleep disturbance and development of mental illness. Objective: The present study examined the longitudinal relationship between sleep disturbance and PTSD symptomatology in a cohort of Marines and Navy Corpsmen deployed to Iraq and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 65 publications
0
20
1
Order By: Relevance
“…SD observed in PTSD are associated with sleep-related arousal regulation (Mellman, 1997 ) and include insomnia, nightmares, hyperarousal states, sleep terrors and nocturnal anxiety attacks, body-movement and breathing-related sleep disorders (Harvey, Jones, & Schmidt, 2003 ; Maher, Rego, & Asnis, 2006 ; Mellman & Hipolito, 2006 ; Pillar, Malhotra, & Lavie, 2000 ; Spoormaker & Montgomery, 2008 ; Westermeyer et al, 2010 ), with heightened sympathovagal tone during rapid-eye-movement (REM) sleep, fragmented REM sleep patterns, reduced REM theta activity (Cowdin, Kobayashi, & Mellman, 2014 ; Germain, 2013 ; Germain et al, 2008 ; Kobayashi, Boarts, & Delahanty, 2007 ; Lamarche & De Koninck, 2007 ; Mellman et al, 2002 ; Mellman & Hipolito, 2006 ) and altered EEG spectral topology (de Boer et al, 2019 ). Interestingly, SD (e.g., disrupted REM sleep, self-reported insomnia and general sleep quality problems) immediately after (Koren, Arnon, Lavie, & Klein, 2002 ; Luik, Iyadurai, Gebhardt, & Holmes, 2019 ; Mellman et al, 2002 , Mellman & Hipolito, 2006 ), as well as prior to trauma exposure could both increase the risk of PTSD development (Acheson et al, 2019 , Bryant, Creamer, O’Donnell, Silove, & McFarlane, 2010 , Koffel, Polusny, Arbisi, & Erbes, 2013 ). Self-reported SD prior to trauma, in particular, has been associated with a 2.5-fold increased risk of PTSD 3 months later in both general population or deployed military troops (Bryant et al, 2010 ; Koffel et al, 2013 ).…”
Section: Stress and Circadian Dysregulationmentioning
confidence: 99%
“…SD observed in PTSD are associated with sleep-related arousal regulation (Mellman, 1997 ) and include insomnia, nightmares, hyperarousal states, sleep terrors and nocturnal anxiety attacks, body-movement and breathing-related sleep disorders (Harvey, Jones, & Schmidt, 2003 ; Maher, Rego, & Asnis, 2006 ; Mellman & Hipolito, 2006 ; Pillar, Malhotra, & Lavie, 2000 ; Spoormaker & Montgomery, 2008 ; Westermeyer et al, 2010 ), with heightened sympathovagal tone during rapid-eye-movement (REM) sleep, fragmented REM sleep patterns, reduced REM theta activity (Cowdin, Kobayashi, & Mellman, 2014 ; Germain, 2013 ; Germain et al, 2008 ; Kobayashi, Boarts, & Delahanty, 2007 ; Lamarche & De Koninck, 2007 ; Mellman et al, 2002 ; Mellman & Hipolito, 2006 ) and altered EEG spectral topology (de Boer et al, 2019 ). Interestingly, SD (e.g., disrupted REM sleep, self-reported insomnia and general sleep quality problems) immediately after (Koren, Arnon, Lavie, & Klein, 2002 ; Luik, Iyadurai, Gebhardt, & Holmes, 2019 ; Mellman et al, 2002 , Mellman & Hipolito, 2006 ), as well as prior to trauma exposure could both increase the risk of PTSD development (Acheson et al, 2019 , Bryant, Creamer, O’Donnell, Silove, & McFarlane, 2010 , Koffel, Polusny, Arbisi, & Erbes, 2013 ). Self-reported SD prior to trauma, in particular, has been associated with a 2.5-fold increased risk of PTSD 3 months later in both general population or deployed military troops (Bryant et al, 2010 ; Koffel et al, 2013 ).…”
Section: Stress and Circadian Dysregulationmentioning
confidence: 99%
“…Cox et al [72] found that the association between the severity of combat exposure and re-experiencing symptoms became stronger with increased degrees of insomnia symptoms. Another study found that sleep disturbances in soldiers before deployment predicted the degree of re-experiencing symptoms post-deployment [73]. Studies recording day-to-day variations in sleep have found that participants with PTSD had increased intrusion symptomology after nights with shorter sleep duration [74], and that mindwandering in general increases after nights with poor sleep [75].…”
Section: Factors During Sleep That Make Memories More or Less Intrusivementioning
confidence: 99%
“…Information regarding these factors and participants' chronotype (i.e., endogenous circadian rhythms) was unfortunately not collected, while known to influence cortisol's diurnal rhythm including the CAR (Dayan, Rauchs, & Guillery-Girard, 2016;Germain, McKeon, & Campbell, 2017;Koch, Leinweber, Drengberg, Blaum, & Oster, 2017;Landgraf, McCarthy, & Welsh, 2014). Moreover, it would have been interesting to assess whether these factors moderated the longitudinal associations between cortisol output and symptom development, as there is increasing evidence linking inter-individual differences in sleep quality, sleep quantity and circadian rhythm to differential susceptibility for developing mental health problems (Acheson et al, 2019;Dayan et al, 2016;Germain et al, 2017;Koch et al, 2017;Landgraf et al, 2014;Lewis et al, 2020;Teicher et al, 2017). Nevertheless, as we observed that the amount of deployment-related traumatic exposure (combined with prior trauma) significantly impacted the cortisol decrease and as pre-deployment symptom levels were generally low, we remain confident that we captured the actual effects of deployment-related trauma exposure and associated changes in symptom severity.…”
Section: Discussionmentioning
confidence: 99%